Role of surface charge and oxidative stress in cytotoxicity of organic monolayer-coated silicon nanoparticles towards macrophage NR8383 cells - Bhattacharjee, Sourav (BioMed Central, 2010)
BACKGROUND: Surface charge and oxidative stress are often hypothesized to be important factors in cytotoxicity of nanoparticles. However, the role of these factors is not well understood. Hence, the aim of this study was to systematically investigate the role of surface charge, oxidative stress and possible involvement of mitochondria in the production of intracellular reactive oxygen species (ROS) upon exposure of rat macrophage NR8383 cells to silicon nanoparticles. For this aim highly monodisperse (size 1.6 ± 0.2 nm) and well-characterized Si core nanoparticles (Si NP) were used with a surface charge that depends on the specific covalently bound organic monolayers: positively charged Si NP-NH(2), neutral Si NP-N(3 )and negatively charged Si NP-COOH. RESULTS: Positively charged Si NP-NH(2 )proved to be more cytotoxic in terms of reducing mitochondrial metabolic activity and effects on phagocytosis than neutral Si NP-N(3), while negatively charged Si NP-COOH showed very little or no cytotoxicity. Si NP-NH(2 )produced the highest level of intracellular ROS, followed by Si NP-N(3 )and Si NP-COOH; the latter did not induce any intracellular ROS production. A similar trend in ROS production was observed in incubations with an isolated mitochondrial fraction from rat liver tissue in the presence of Si NP. Finally, vitamin E and vitamin C induced protection against the cytotoxicity of the Si NP-NH(2 )and Si NP-N(3), corroborating the role of oxidative stress in the mechanism underlying the cytotoxicity of these Si NP. CONCLUSION: Surface charge of Si-core nanoparticles plays an important role in determining their cytotoxicity. Production of intracellular ROS, with probable involvement of mitochondria, is an important mechanism for this cytotoxicity.